PENGARUH MANAJEMEN LABA, TANGGUNG JAWAB SOSIAL PERUSAHAAN, DAN KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Sektor Basic Material Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Nur ‘Ain, Masyithah; Nasir, Azwir; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This research aims to provide empirical evidence regarding the influence of EarningManagement, Coorporate Social Responsibility, and Independent Commissioner on FirmValue. The population in this research are all basic material sector companies listed on theIndonesian Stock Exchange for the 2021-2023 period. With the purposive sampling method,the sample in this research was 17 companies. The data analysis technique used in thisresearch is multiple linear regression analysis. Data processing was carried out using SPSSVersion 24. The results of this research show that earning management, Corporate SocialResponsibility, and independent commissioner has no effect on firm value.Keywords: Earning Management, CSR, Independent Commissioner, and Firm Value.